Dynamics of Islamic Pesantren: Digital Marketing Strategy Model on the Existence of Santripreneur Roles: Dinamika Pesantren: Model Strategi Digital Marketing Pada Eksistensi Peran Santripreneur - Retnowati, May Shinta; Qoharuddin, Moch. Azis; Yusuf, M. Asror; Humaidi, Anis (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2025)
Pesantren today not only serve as institutions for Islamic education, but also play a role in the aspects of community life. Santripreneur has become one of the roles of santri in the economic independence of pesantren, with digital marketing being one of the distinguishing features of the typical muamalah of santri with society in general.The purpose of this research is to explore the role of Santris in addressing the challenges of the digital world, particularly in the aspect of digital marketing which has become one of the sources of income for the Santris with the pesantren strategy model. This research method uses a qualitative approach with descriptive analysis. Data obtained from interviews with religious leaders, instructors, and students. The results of this study show the efforts of pesantren in shaping santripreneurs who carry out digital marketing, activities that embody the spirit of the pesantren. The spirit of the pesantren is the identity of the santri who continue to uphold the values of the pesantren, indicating a significant dynamic within the pesantren regarding the existence of santri who are capable of engaging in digital business aspects, particularly in marketing. The marketing strategy of the santri optimizes the digital competencies possessed by the santri that are inherent to the pesantren, focusing on optimizing marketing content on social media and e-commerce.